Pujangga (Kraton) Jawa Vs Agen dalam Pandangan Bordieu - Arsanti Wulandari (Masyarakat Pernaskahan Nusantara, 2017)
Generally, among the Javanese kingdom, there are poets who are employed specifically to produce texts or engage in the process of creating texts within the palace. These poets are the